Shape-Preserving Techniques with Fractional Order C1 Linear Trigonometric Spline - Kirmani, Syed Khawar Nadeem; Jamil, Raja Noshad; Muhammad, Awais (Scientific Inquiry and Review, 2024)
Generating a smooth curve or surface is the prime goal of interpolation. If the given interplant reflects the exact shape of the data, it would be an added advantage. In this study, a general form of Fractional Order Linear Trigonometric Spline (FOLTS) is proposed with continuity. A method for modeling imperative curves has been developed with the goal of using it in a variety of engineering, scientific, and design fields. The primary goal of this research is to combine linear trigonometric spline with Caputo derivative in order to obtain better control over the curve in each sub-interval. The curve can be manipulated locally with the help of one degree of freedom involved in the form of fractional parameters. To describe shape-preserving interpolation applications, two more parameters namely “s” and “t” have been developed. These parameters ensure that the interpolated piecewise curve is able to satisfy shape-preserving properties. The study also compares FOLTS with quadratic Lagrange and cubic spline.